Multidirectional analysis, causal relationship influencing the Effectiveness of support personnel Ramkhamhaeng University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this study were to: 1) analyze the causal relationship pathway having influence on effectiveness of supporting personnel at Ramkhamhaeng University, and 2) verify the causal factor hypothesis having influence on the supporting personnel.  The sample group consisted of 300 supporting personnel at Ramkhamhaeng University. The researchers gained 30 causal variables having influence on the supporting personnel and the sample group size was ten times of the variable.  A set of questionnaires was used for data collection and analyzed by using frequency, percentage, mean, and standard deviation.  Besides, path analysis was conducted by using the AMOS program.Results of the study revealed that he conceptual framework of causal factor relationship having influence on effectiveness of the supporting personnel comprised 2 variables having direct influence: nature of work and quality of work life and 7 variables having both direct and indirect influence : 1) safe and health promotion environment, 2) an individual capability development, 3) social integration, 4) statue in the organization, 5) relationship with society, 6) uniqueness of the work, and 7) reflection from work.  The hypothetical model was work consistent with the empirical data based on the CMIN/df was equivalent to 1.465; p-value = .913; GFI = .960; RMSCA = 0.000; NFI = .957; TLI = .968; and CFI = .984.  The total influence of the causal variable having influence on effectiveness of the supporting personnel most was nature of work and followed by quality of work life.  All of the components could explain variance effectiveness of the supporting staff for 88.30 percent.